Impact of Personal and Situational Factors on Taxpayer Compliance: An Experimental Analysis - Trivedi, V. Umashanker (Journal of business ethics, 2003)
This study used a laboratory experiment with monetary incentives to test the impact of three personal factors (moral reasoning, value orientation and risk preference), and three situational factors (the presence/absence of audits, tax inequity, and peer reporting behavior), while controlling for the impact of other demographic characteristics, on tax compliance. Analysis of Covariance (ANCOVA) reveals that all the main effects analyzed are statistically significant and robustly influence tax compliance behavior. These results highlight the importance of obtaining a proper understanding of these factors for developing effective policies for increasing the level of compliance, and indicate that standard enforcement polices based on punishment alone should be supplemented by an information system that would acquaint tax payers with the compliance level of other tax payers; reinforce the concept of fairness of the tax system among tax payers; and develop programs that enhance and appeal to a taxpayer's moral conscience and reinforce social cohesion.